Costo-Efectividad De Exploración De Miembros Pélvicos Para Prevenir Pie Diabético - Prishila Danae, Reyes-Chávez; Enrique, Villarreal-Ríos; Martha Leticia, Martínez-Martínez; Jorge, Velázquez-Tlapanco; Nicolás, Camacho-Calderón; Lilia Susana, Gallardo-Vidal; Azucena, Bello-Sánchez Ma.; Miguel Ángel, Narváez-Escobedo; Nora, Azpeitia-Castillo (European Scientific Journal, ESJ, 2016)
Diabetic neuropathy is a common and frequent complication of DM2. It is the main risk factor for ulcer and amputation of lower limbs. The risk of developing ulcer foot is 12 -25%. In the first level of care medical, history and physical examination of the patient with DM2 is performed to determine the appropriate treatment. Objective: Determine the costeffectiveness of the exploration of pelvic limbs to prevent diabetic foot. Materials and Methods: Cost-effectiveness design. Clinical records of patients with DM2. Sample calculation with the formula of percentages of two populations. Group 1, complete scan of pelvic limbs (n=15) and Group 2 with incomplete examination of lower limbs (n=40). Sociodemographic variables, health characteristics, type and number of laboratory studies requested, type and quantity of drugs prescribed were analyzed. The effectiveness was evaluated as absence of data from diabetic foot in five years follow- up. The cost of care was estimated with the profile of use and unit cost. Statistical analysis averages, percentages and cost-effectiveness. Results: The total cost in group 1 was 7,203.24 and 4,909.03 in 2. Group 1, the total cost in laboratory studies was 5,863.44, 187.62 in drugs and average cost of 1,152.18 in consultation; while in the 2, laboratory it was 3,596.76 , 186.24 medicines and average cost of consultation 1,126.03. The effectiveness for 5,000.00 in group 1 corresponds to 37.00 and in the group 2 to 79.75. Conclusions: It was no scanning showed that full pelvic limbs and timely detection of diabetic foot out cost-effective.